Assessing Health Research and Innovation Impact: Evolution of a Framework and Tools in Alberta, Canada - Graham, Kathryn E. R.; Langlois-Klassen, Deanne; Adam, Sagal A. M.; Chan, Liza; Chorzempa, Heidi L. (Frontiers in Research Metrics and Analytics, 2018)
Publicly funded research and innovation (R&I) organizations around the world are facing increasing demands to demonstrate the impacts of their investments. In most cases, these demands are shifting from academically based outputs to impacts that benefit society. Funders and other organizations are grappling to understand and demonstrate how their investments and activities are achieving impact. This is compounded with challenges that are inherent to impact assessment, such as having an agreed understanding of impact, the time lag from research to impact, establishing attribution and contribution, and consideration of diverse stakeholder needs and values. In response, many organizations are implementing frameworks and using web-based tools to track and assess academic and societal impact. This conceptual analysis begins with an overview of international research impact frameworks and emerging tools that are used by an increasing number of public R&I funders to demonstrate the value of their investments. From concept to real-world, this paper illustrates how one organization, Alberta Innovates, used the Canadian Academy of Health Sciences (CAHS) impact framework to guide implementation of its fit-for-purpose impact framework with an agnostic international six-block protocol. The implementation of the impact framework at Alberta Innovates is also supported by adopting emerging web-based tools. Drawing on the lessons learned from this continuous organizational endeavour to assess and measure R&I impact, we present preliminary plans for developing an impact strategy for Alberta Innovates that can be applied across sectors, including energy, environment and agriculture, and may possibly be adopted by other international funders.